Vocational education and training for sustainable development : train the trainers in Germany - Mareike Beer [Verfasser]; Ritters, Alexandra [Verfasser]; Thieme-Hack, Martin [Verfasser] (My University, 2024)
“The topic of sustainability and the concept of Vocational Education for Sustainable Development (VESD) play a major role in dual vocational education and training in Germany, especially due to the modernised occupational profile items on environmental protection and sustainability introduced in 2020. This article presents didactic approaches to the design and organizational embedding of measures aimed at developing and expanding the skills of VET personnel related to sustainability. Furthermore, an outlook is provided on an implementation project in the training occupation of gardener, demonstrating how the content of sustainable management can be integrated with qualification programs for in-company and inter-company trainers.” (authors’ abstract; BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; P 3.2 Lehrpersonal; 370; Nachhaltige Entwicklung; Ausbilder; Bildungspersonal; Kompetenzentwicklung; Qualifizierung; Gärtner